2013
DOI: 10.1007/s11274-013-1564-1
|View full text |Cite
|
Sign up to set email alerts
|

Fusaric acid accelerates the senescence of leaf in banana when infected by Fusarium

Abstract: Fusarium oxysporum f.sp. cubense (FOC) is a causal agent of vascular wilt and leaf chlorosis of banana plants. Chloroses resulting from FOC occur first in the lowest leaves of banana seedlings and gradually progress upward. To investigate the responses of different leaf positions to FOC infection, hydroponic experiments with FOC inoculation were conducted in a greenhouse. Fusarium-infected seedlings exhibited a decrease in net photosynthesis rate, stomatal conductance, and transpiration rate of all leaves. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
1
34
0
1
Order By: Relevance
“…The production and phytotoxic properties of FA have been studied over the past 75 years (Bacon et al, 1996;Dong et al, 2014;G€ aumann, 1957, 1958Yabuta et al, 1937), and a number of mechanisms for FA toxicity have been suggested, most related to modifications in the plant cell membrane (D'Alton and Etherton, 1984). To test FA toxicity, roots of 3-week-old tomato plants were immersed in sterile water with or without FA.…”
Section: Fa Toxicity In Tomato Plants Is Reversed By the Exogenous Admentioning
confidence: 99%
See 1 more Smart Citation
“…The production and phytotoxic properties of FA have been studied over the past 75 years (Bacon et al, 1996;Dong et al, 2014;G€ aumann, 1957, 1958Yabuta et al, 1937), and a number of mechanisms for FA toxicity have been suggested, most related to modifications in the plant cell membrane (D'Alton and Etherton, 1984). To test FA toxicity, roots of 3-week-old tomato plants were immersed in sterile water with or without FA.…”
Section: Fa Toxicity In Tomato Plants Is Reversed By the Exogenous Admentioning
confidence: 99%
“…FA is one of the first fungal toxins for which a functional role in virulence has been proposed (G€ aumann, 1957, 1958) and several studies have provided circumstantial evidence linking FA production to plant pathogenicity (Dong et al, 2014;Gapillout et al, 1996;Venter and Steyn, 1998). However, to date, no formal proof for such a role has been provided.…”
Section: Mechanism Of Fa Phytotoxicity and Role In Virulencementioning
confidence: 99%
“…Foc stimulates pathogen-induced necrosis in later stages of infection However, wilt causing Fusarium fungi shows a short biotrophic phase during establishment in the host plant and later enters the necrotrophic phase, thereby making it a hemibiotroph (Thaler et al 2004;Bhadauria et al 2009). Plant cell death also occurs due to potent phytotoxins such as fusaric acid (Laluk & Mengistea 2010) and beauvericin (BEA) (Li et al 2011b;Li et al 2013a;Dong et al 2014) secreted by Foc during infection. Fusaric acid is a known potent phytotoxin that induces senescence in the infected banana leaves (Dong et al 2014), whereas BEA inhibits cholesterol acyltransferase and induces typical programmed cell death.…”
Section: Fusarium Wilt Disease Cyclementioning
confidence: 99%
“…Plant cell death also occurs due to potent phytotoxins such as fusaric acid (Laluk & Mengistea 2010) and beauvericin (BEA) (Li et al 2011b;Li et al 2013a;Dong et al 2014) secreted by Foc during infection. Fusaric acid is a known potent phytotoxin that induces senescence in the infected banana leaves (Dong et al 2014), whereas BEA inhibits cholesterol acyltransferase and induces typical programmed cell death. BEA also induces pore formation in biological membranes (Wu et al 2008;Stenglein 2009;Stipanovic et al 2011).…”
Section: Fusarium Wilt Disease Cyclementioning
confidence: 99%
“…It was indicated by the development of wilting or yellowing leaves (Dong et al, 2012). Fusaric acid was a phytotoxin produced by Foc which disrupted the permeability of plant membrane, inhibited the oxygen taking and had important role as causal agent of yellowing leaves and enhanced the aging process on infected plants (Dong et al, 2014).…”
Section: Disease Progressmentioning
confidence: 99%